Pengembangan Kemampuan Bahasa Anak Usia Dini: Peran dan Problematika Guru dalam Pembelajaran - Zawaqi Afdal Jamil; Medina Yuliastri; Yusria (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study aims to identify the challenges faced by teachers in developing children's language skills and to explore the efforts made to overcome these obstacles through adaptive teaching methods. Using a descriptive qualitative approach, data were collected through observations, in-depth interviews, and document analysis. The research participants included teachers, parents, and students at TK An-Nur, Kerinci Regency, representing the learning ecosystem. Data analysis employed the flow model analysis, consisting of data reduction, data presentation, and conclusion drawing. The findings reveal that the main barriers to children's language development include limited instructional time, lack of resources, variation in children's language abilities, and minimal parental support. These factors significantly affect children's language development and require specific strategies to create a more effective learning environment.